Associations of the Severity of Obstructive Sleep Apnea With Age-Related Comorbidities: A Population-Based Study - Silva, Mayra dos Santos; Poyares, Dalva; Silva, Luciana Oliveira; Souza, Ksdy M.; Andersen, Monica L.; Ohayon, Maurice M.; Tufik, Sergio; Piovezan, Ronaldo D. (Frontiers in Neurology, 2022)
Aging is accompanied by changes in the quantity and quality of sleep. Obstructive sleep apnea (OSA) is also more prevalent in the older population. Although severe OSA has been linked to higher risk of cardiovascular disease regardless of adult age, clinical consequences of mild to moderate OSA in the older adults are still uncertain. Objectives: To investigate the relationships between OSA severity and metabolic, cognitive and functional characteristics in community dwelling older adults from a representative sample of the city of Sao Paulo. Methods: 199 participants of the first follow-up of the EPISONO (São Paulo, Brazil) >60 years were cross-sectionally assessed through questionnaires, physical evaluations, laboratory tests, and full in-lab polysomnography (PSG). Three groups according to OSA severity were compared according to participant’s characteristics including socio-demographic characteristics, anthropometric measures, PSG parameters, frequency of comorbidities and use of medications. Results: Participants’ age ranged from 60 to 87 year with a mean of 70.02±7.31, 59,8% female. In the univariate analysis, body mass index, (BMI, Kg/m2) (p=0.049) and waist circumference (p=0.005) were significantly higher in the participants with moderate OSA, but not among those with severe OSA. Participants with severe OSA had higher arousal index (p=0.007). Multivariate analysis showed that severe OSA was significantly associated with hypertension (p=0.005), heart diseases (p=0.025), and the use two or more medications (p=0.035). Conclusion: In a population-based study, severe but not mild-to-moderate OSA in older adults was associated with hypertension and use of more medications. As age advances, anthropometric indicators of obesity may not increase the risk severe OSA.